Fluorescence in situ hybridization compared with conventional cytology for the diagnosis of malignant biliary tract strictures in Asian patients - Roongruedee Chaiteerakij (2018)
© 2016 American Society for Gastrointestinal Endoscopy. Background and Aims Fluorescence in situ hybridization (FISH) has improved the diagnostic performance of cytology for the evaluation of malignant biliary strictures in the United States and Europe. The utility of FISH for the diagnosis of biliary strictures in Asia is currently unknown. We aimed to compare the sensitivity of FISH and conventional cytology for the diagnosis of malignant biliary strictures in Thai patients. Methods A prospective study was performed at 2 university hospitals between 2010 and 2013. Patients being evaluated for malignant-appearing biliary strictures were included (N = 99). Bile duct brushings were collected and assessed by cytology and FISH. Sensitivities with 95% confidence intervals of cytology and FISH were the main outcome measures. Results The overall sensitivities of cytology and FISH were 38% and 55%, respectively (P =.001). For those with a diagnosis of cancer based on clinical evidence without biopsy confirmation (n = 44), the sensitivities of cytology and FISH were 43% and 57%, respectively (P =.06). For the 49 patients for whom a cancer diagnosis was confirmed by pathology, FISH had a significantly higher sensitivity than cytology, with a sensitivity of 53% versus 33%, respectively (P =.008). Conclusions FISH improves the diagnostic performance of cytology and can be used as a complementary tool to bile duct brushing and biopsy for the evaluation of malignancy in biliary strictures in Asian populations.